Maternal Low-Protein Diet Deregulates DNA Repair and DNA Replication Pathways in Female Offspring Mammary Gland Leading to Increased Chemically Induced Rat Carcinogenesis in Adulthood - Zapaterini, Joyce R.; Fonseca, Antonio R. B.; Bidinotto, Lucas T.; Colombelli, Ketlin T.; Rossi, André L. D.; Kass, Laura; Justulin, Luis A.; Barbisan, Luis F. (Frontiers in Cell and Developmental Biology, 2022)
Studies have shown that maternal malnutrition, especially a low protein diet (LPD), plays a key role in the developmental mechanisms underlying mammary cancer programming in female offspring. However, the molecular mechanisms are still poorly understood. Thus, this study investigated the adverse effects of gestational and lactational low protein intake on gene expression of key pathways involved in mammary tumor initiation after a low single dose of N-Methyl-N-Nitrosourea (MNU) in prepubertal F1 female offspring rats. Pregnant Sprague-Dawley rats were fed a normal protein diet (NPD) (17% protein) or LPD (6% protein) from gestational day 1 (GD1) to postnatal day (PND) 21. After weaning (PND21), female offspring (n=5, each diet) were euthanized for histological analysis or received NPD (n= 56 each diet). At PND 28 or 35, female offspring received a low single dose of MNU (25 mg/kg b.w.) (n=28 each diet/time-point). After 24 hours, some females (n=10 each diet/time-point) were euthanized for histological, immunohistochemical, and molecular analyses. The remained animals (n=18 each diet/time-point) were euthanized when tumors reached ≥ 2cm or until PND 250. Besides the mammary gland development delay observed in LPD groups at PND 21 and 28, the gene expression profile demonstrated that maternal LPD deregulated twenty-one genes related to DNA repair and DNA replication pathways in the mammary gland at PND 36. We further confirmed an increased γ-H2AX (DNA damage biomarker) and in ER-α immunoreactivity in mammary epithelial cells in LPD group at PND 36. Furthermore, these early postnatal events were followed by a significantly increased mammary tumor incidence in offspring at adulthood. Thus, the results indicate that gestational and lactational LPD influenced the programming chemically-induced mammary carcinogenesis in female offspring through DNA damage increase and deregulation of DNA repair and DNA replication pathways. The upregulation of Cidea gene in LPD 35 group was also confirmed as a predictive biomarker of poor prognosis correlated with survival for patients with breast cancer. These findings increase the body of evidence of early-transcriptional mammary gland changes influenced by maternal LPD, resulting in differential response to breast tumor initiation and susceptibility and may raise discussions about lifelong prevention of breast cancer risk.